Substitution and electron transfer in diborane-quinone systems - Vogler, Daniel; Krauß, Julian; Kaczun, Tobias; Dulatahu, Gent; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2025)
The dual reactivity of boron compounds as Lewis acids and electron donors has spurred the development of a metallomimetic chemistry of boron compounds as a topical research theme. In this work we elaborate on the reaction of specially-designed diborane(4) compounds with quinones, as a prime example showing their dual (metallomimetic) chemistry as a Lewis acid and electron donor. The quinone is first coordinated to the diborane and then reduced by intramolecular electron transfer from the B−B bond to a quinone π* orbital. A variety of substitution reactions of the catecholate-diborane reaction product was carried out, leading to new catecholato-diborane compounds and thereby shedding light on the likely mechanisms. Notably, the results disclose the importance of a facile coordination-mode change of the catecholato ligand (end-on to bridging) for substitution reactions and for the diborane-quinone reactions. The results contribute to the further advancement in the use of diboranes with dual reactivity for substrate binding and reduction.